Optimizing fertilizer compounds for pineapple production using the goal programming approach / Farzana Mohd Ezan … [et al.] - Mohd Ezan, Farzana; Shafii, Nur Hanani; Juani, Nurfatihah; Latif, Busyra (Universiti Teknologi MARA Cawangan Pahang, 2020)
Pineapple, a fruit under the Bromeliaceae family, is one of the most popular tropical fruits in Malaysia. Similar to other fruits, it requires fertilizer to grow efficiently. Fertilizer is any material of synthetic origin that is applied to soils. The function of fertilizer in growing plants is to increase tissues supply and increase necessary nutrients to the plants. The aim of this research is to reduce the overall fertilizer expense in pineapple plantation and reduce nitrogen-phosphorus-potassium (NPK) fertilizer’s utilization (upper and lower limits) via the Goal Programming (GP) algorithm. The study focuses only on cultivation of one type of crop which is pineapples. Five fertilizers with different contents of NPK were analyzed. The result showed that 107.73 kg/ha of NPK 16/16/16, 102.92 kg/ha of Special Red, 85.47 kg/ha of NPK 44, 101.07 kg/ha of NPK Green and 90.58 kg/ha of NPK Blue are necessary to optimize pineapple production. This combination can help farmers to use the right amount of NPK fertilizers in pineapple production and reduce overall cost of production.